A simulation of loading doses for vancomycin continuous infusion regimens in intensive care - Šíma, Martin; Hronová, Karolína; Hartinger, Jan; Slanař, Ondřej (Infectious diseases (London, England), 2017)
BACKGROUND: Delayed achievement of target vancomycin serum concentrations may adversely affect clinical outcomes. The objective of this retrospective study was to compare the prediction accuracy of different body weight descriptors for volume of distribution and to propose an optimal loading dose (LD) for continuous infusion regimens in adults. METHODS: Pharmacokinetic variables were computed using one-compartmental analysis. Simulated LDs of vancomycin were evaluated for each patient. RESULTS: Volume of distribution, clearance, and half-life median values (interquartile range) for vancomycin in the study population (n = 30) were 0.45 (0.39-0.61) L.kg-1, 0.026 (0.015-0.040) L.h-1.kg-1, and 10.3 (7.7-21.3) h, respectively. The observed volume of distribution was better predicted by total body weight (TBW) than by the ideal body weight or the adjusted body weight. CONCLUSIONS: An LD of 10.7 mg per kg TBW was optimal in our study population. Using this LD, 17.9% of simulated vancomycin serum levels were just below the therapeutic range, only 10.7% concentrations exceeded the target range and no concentration was toxic. The use of a LD would lead to reduced median time to reach target concentrations from 17 to 1 h.
Keywords: obezita; vankomycin; poločas; Humans; lidé středního věku; Computer Simulation; Dose-Response Relationship, Drug; Female; Aged; Critical Care; pharmacokinetics; senioři; péče o pacienty v kritickém stavu; lidé; Half-Life; body weight; Vancomycin; continuous infusion; volume of distribution; počítačová simulace; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Infusions, Intravenous; Obesity; vztah mezi dávkou a účinkem léčiva; retrospektivní studie; Body Weight; tělesná hmotnost; mužské pohlaví; obesity; intravenózní infuze